PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA ANGGOTA SATUAN POLISI PAMONG PRAJA KABUPATEN NIAS SELATAN - Halawa, Romelius (Jurnal Ilmiah Mahasiswa Nias Selatan, 2025)
This research aims to determine the effect of compensation and work motivation on job satisfaction of South Nias Regency Civil Service Police Unit Members. This type of research is causal quantitative research. The sampling technique used is probability sampling with a random sampling technique. The sample in this study consisted of 30 members of the Civil Service Unit. The analytical method used in this research is multiple linear regression analysis. The results of this research show that partially and simultaneously compensation and work motivation have a significant effect on job satisfaction. The conclusion is that compensation and work motivation influence the job satisfaction of members of the South Nias Regency Civil Service Police Unit. The suggestion in this research is, in order for members of the Civil Service Police Unit to work better, it is best that the compensation given as remuneration for the services provided to them be adjusted to the work results and responsibilities given to them and so that members of the Civil Service Police Unit are not discouraged. The compensation given is fair based on the same work duties between colleagues